WOM as The Mediator of Marketing Mix to Customer Satisfaction in Covid-19 Pandemic - Haryati, Novi; Putri, Rosita Widya; Syah, Nisrina Qotrunnada Yafi Alam; Ramadhani, Mirza; Nugroho, Bagus Cahyo (International Research Journal of Business Studies, 2021)
This study examines coffee shops’ marketing mix and its impact towards customer satisfaction and word of mouth. Also, analyzing customer satisfaction mediates the relationship between the marketing mix and word of mouth. This study used a quantitative approach with 100 sampling of coffee shop’s customers across Malang City. Primary data collection is done by distributing questioner contained with several questions using a Likert scale to the respondents, while secondary data is obtained from literature studies. For analyzing the data, this study applied descriptive analysis and statistical analysis employed WarpPLS 7.0 software to perform the Partial Least Squares-Structural Equation Modelling (PLS-SEM) analysis. This study proves that marketing mix has a positive and significant effect on customer satisfaction, and the same relationship was found between the marketing mix and word of mouth. An important finding from this study is that customer satisfaction plays a mediating role between marketing mix and word of mouth.